Carrageenan-based adsorption material, preparation method thereof and application of carrageenan-based adsorption material in antibiotic / heavy metal dual adsorption
By grafting natural melanin on the κ-carrageenan network and performing physical-chemical double crosslinking, the porous structure of Mel/Ma-κca adsorbent was prepared, which solved the problems of irreversibility and secondary contamination of existing gel materials during chemical crosslinking, and achieved efficient antibiotic/heavy metal adsorption and good biocompatibility.
Patent Information
- Application Number
- CN202510016718.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-14
AI Technical Summary
The existing natural macromolecular gel materials have irreversibility and the use of toxic chemical crosslinking agents during chemical crosslinking, which leads to poor self-repairing performance and biocompatibility. At the same time, melanin, as a powder-like adsorption material, is difficult to separate from the solution, and is prone to secondary contamination.
The physical-chemical hybrid crosslinking method is used to graft natural melanin into the κ-carrageenan network of the physical-chemical dual crosslinking system, and a "microlyophilization" regulation program is performed by a freeze-dryer to prepare a natural melanin/methacrylate-κ-carrageenan (Mel/Ma-κca) adsorbent with a porous structure.
The good swelling performance, stability and efficient dual adsorption of the adsorbed material are achieved, which avoids secondary pollution and improves the self-repairing performance and biocompatibility of the material.
Smart Images

Figure CN119608120A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a carrageenan-based adsorption material, a preparation method thereof, and application thereof in antibiotic / heavy metal dual adsorption. Background Art
[0002] κ-carrageenan (κca) is a water-soluble polysaccharide extracted from marine red algae. Because it has hydrophilic colloids with sulfonic acid groups, hydrophilic groups and a three-dimensional network structure, it can swell rapidly in aqueous solutions and is conducive to shortening the time to reach adsorption equilibrium. Therefore, it has become a natural macromolecule commonly used in synthetic gel materials. Polymer gel materials prepared by physical crosslinking of natural macromolecules have excellent fatigue resistance and self-healing properties, and are therefore favored by researchers. Polymer gel materials prepared by chemical crosslinking of natural macromolecules have extraordinary mechanical properties, but due to the irreversibility of chemical crosslinking and the use of toxic chemical crosslinking agents, most gel materials have poor self-healing properties and biocompatibility.
[0003] Melanin (Mel) is a multifunctional composite polymer composed of phenols, which is widely found in animals, plants and microorganisms. Melanin has many excellent properties, such as high temperature resistance, radiation resistance and antibacterial properties. The excellent properties of melanin make it have intrinsic advantages in environmental remediation materials under complex natural conditions. However, Mel is a powdered bioadsorption material, which makes the separation of adsorbent and solution very difficult in practice and easily causes secondary pollution.
[0004] In view of the above problems, the present invention designs a physical-chemical hybrid cross-linking method, grafts natural melanin into the κ-carrageenan network of the physical-chemical double cross-linking system, uses a freeze dryer to perform a "micro-freeze-drying" control procedure, and prepares a natural melanin / methacrylate-κ-carrageenan (Mel / Ma-κca) adsorbent with a porous structure. Summary of the invention
[0005] The purpose of the present invention is to provide a carrageenan-based adsorption material and a preparation method thereof and application in antibiotic / heavy metal dual adsorption, so as to solve the problems raised in the above-mentioned background technology. On the basis of potassium ion crosslinking, κca is chemically functionalized using the photosensitive group of methacrylic anhydride (Ma), thereby designing a polymer gel of a physical-chemical dual crosslinking system, and Mel is grafted and assembled on its polymer network, thereby obtaining an adsorption material with good swelling performance, stability and no secondary pollution.
[0006] To achieve the above object, the present invention provides a method for preparing a carrageenan-based adsorption material, comprising the following steps: (1) Extraction of natural melanin from apricot shell; (2) Using the Ma photosensitive group to esterify κca to synthesize Ma-κca; (3) The extracted natural melanin is grafted onto the Ma-κca network to prepare the melanin / Ma-κca porous gel adsorption material.
[0007] Preferably, the specific operation of step (1) is: The dried apricot shell is crushed and sieved, dissolved in NaOH solution at a solid-liquid ratio of 1:15, and the solid is removed after standing. The pH of the supernatant is adjusted with dilute HCl, and the supernatant is removed after standing and settling. The pH of the precipitate is adjusted with deionized water, and then 0.1% of cellulase and saccharifying enzyme are added. The supernatant is removed by centrifugation after heating in a water bath, and NaOH solution is added to the enzyme-treated solid at a solid-liquid ratio of 1:20, ultrasonically dissolved, acid precipitated and centrifuged to remove the supernatant. The solid obtained after drying is melanin, which is sealed in a dark place.
[0008] Preferably, the concentration of NaOH solution is 2 mol / L, the pH is adjusted to 2.2 with dilute HCl, the pH is adjusted to 5.0 with deionized water, the solution is heated to 60° C. in a water bath, and sealed at 4° C. to avoid light.
[0009] Preferably, the specific operation of step (2) is: κca with a mass volume percentage concentration of 2% was added to deionized water and dissolved at 80°C, and then Ma was added to react at 50°C. The pH value of the solution was kept constant during the reaction. After the reaction was completed, dialyzed to obtain a pure Ma-κca solution, which was freeze-dried and stored away from light.
[0010] Preferably, the pH value of the solution is 8.0; the dialysis conditions are: dialysis at 4°C for 3 days using a 14 kDa cut-off dialysis bag; the freeze-drying temperature is -80°C, and the storage temperature is -20°C.
[0011] Preferably, the specific operation of step (3) is: The Ma-κca macromer and unmodified κca were added to a photoinitiator with a mass volume percentage concentration of 0.25%, and dissolved at 80°C to obtain a Ma-κca solution. The extracted apricot shell melanin was dissolved in a 2 mol / L NaOH solution, and added to the Ma-κca solution at 50°C with stirring to obtain Mel / Ma-κca. A KCl solution with a mass volume percentage concentration of 5% was added as an initiator to initiate crosslinking to obtain a physically crosslinked Mel / Ma-κca gel, which was then rapidly poured into a mold after ultraviolet irradiation to complete the photocrosslinking reaction to obtain a physically-chemically double crosslinked Mel / Ma-κca gel. The gel was washed with deionized water after cooling, and the surface moisture was dried and stored in a frozen state away from light.
[0012] Preferably, the freezing process is: first transferred to a -20°C freeze dryer for freezing for 2 hours, and then transferred to a -50°C freeze dryer for freezing for 1 hour.
[0013] The present invention also provides a carrageenan-based adsorption material prepared by the above preparation method.
[0014] The present invention also provides the use of the carrageenan-based adsorption material in the adsorption of antibiotics and heavy metals.
[0015] Therefore, the carrageenan-based adsorption material and its preparation method and application in antibiotic / heavy metal dual adsorption provided by the present invention have the following beneficial effects: (1) By designing a physical-chemical hybrid cross-linking method, κca was chemically functionalized using the photosensitive group of methacrylic anhydride (Ma) on the basis of potassium ion cross-linking, thereby designing a polymer gel with a physical-chemical dual cross-linking system, expanding the application of κca in the environmental field.
[0016] (2) Based on the characteristics of the physical-chemical double cross-linking system of κca with a rich network skeleton, natural melanin was grafted and assembled on its polymer network to prepare a natural melanin / methacrylate-κ-carrageenan (Mel / Ma-κca) adsorbent with a porous structure. This adsorbent has good swelling properties, high stability, and will not cause secondary pollution. It can achieve dual adsorption of antibiotics and heavy metals.
[0017] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 FTIR spectra of Mel, κca, Ma-κca and Mel / Ma-κca porous gel materials in the embodiments of the present invention; Figure 2 The SEM morphology of the κca, Ma-κca and Mel / Ma-κca porous gel materials in the embodiments of the present invention; Figure 3 It is a comparison diagram of TG curves of κca, Ma-κca and Mel / Ma-κca porous gel materials in the embodiment of the present invention; Figure 4 It is a comparison diagram of DTG curves of κca, Ma-κca and Mel / Ma-κca porous gel materials in the embodiment of the present invention; Figure 5 1 is a stress-strain curve diagram of κca, Ma-κca and Mel / Ma-κca porous gel materials in the embodiments of the present invention; Figure 6It is a comparison chart of the swelling performance of κca, Ma-κca and Mel / Ma-κca porous gel materials at different times in the embodiment of the present invention; Figure 7 It is a comparison chart of the swelling properties of κca, Ma-κca and Mel / Ma-κca porous gel materials under different pH conditions in the embodiments of the present invention; Figure 8 This is a comparison chart of swelling degree results of κca, Ma-κca and Mel / Ma-κca porous gel materials in different application scenarios according to the embodiment of the present invention; Fig. 9 This is a comparison chart of the water retention results of κca, Ma-κca and Mel / Ma-κca porous gel materials in different application scenarios in the embodiment of the present invention; Fig.10 FTIR spectra of the Mel / Ma-κca porous gel adsorption material prepared in the embodiment of the present invention before and after adsorption of single / complex pollutants. DETAILED DESCRIPTION
[0019] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0020] The present invention is further described below in conjunction with specific embodiments and accompanying drawings. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, simplifications made without violating the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application, and all belong to the scope of protection of the present invention.
[0021] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.
[0022] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0023] Unless otherwise specified in the present invention, the reagents, instruments, and equipment used are those commonly used by technicians in this field.
[0024] Example This embodiment provides a method for preparing a natural melanin / methacrylate-κ-carrageenan adsorption material with a porous structure, and the specific steps are as follows: (1) Extraction of natural melanin from apricot shell The dried apricot shells were crushed and passed through an 80-mesh sieve. They were dissolved in a 2mol / L NaOH solution at a solid-liquid ratio of 1:15. The solids were removed after standing and extraction. The supernatant was adjusted to pH 2.2 with a dilute hydrochloric acid solution. After standing and settling for 2 hours, the supernatant was removed by centrifugation. Deionized water was used to adjust the pH to 5.0, and 0.1% cellulase and saccharifying enzyme were added. The supernatant was removed by centrifugation after 1 hour of water bath at 60°C. A 2mol / L NaOH solution was added to the enzyme-treated solid at a solid-liquid ratio of 1:20, and ultrasonic-assisted dissolution was performed for 30 minutes. After acid precipitation, the supernatant was removed by centrifugation. The solid obtained after drying was melanin, which was completely sealed in a 4°C environment away from light.
[0025] (2) Synthesis of methacrylate-κ-carrageenan 2% (wt / v) κca was mixed in deionized water at 80°C until completely dissolved. Ma 1% (wt / v) was added to the solution and reacted at 50°C for 6h, and the pH of the reaction was periodically adjusted to maintain 8.0 in the solution. When the esterification reaction was terminated, it was dialyzed at 4°C for 3 days using a 14kDa cut-off dialysis bag to remove unreacted Ma. The purified Ma-κca solution was frozen at -80°C and then freeze-dried, and the resulting freeze-dried powder was stored at -20°C and protected from light until further use.
[0026] (3) Preparation of melanin / methacrylate-κ-carrageenan porous gel Freeze-dried Ma-κca macromers and unmodified κca (3:2) were added to 0.25% (wt / v) photoinitiator Irgacure 2959 at 80°C until completely dissolved. 25 mg of apricot kernel melanin was weighed and dissolved in 2 mol / L NaOH solution and added to the completely dissolved Ma-κca solution at 50°C. Stirring was continued for 2 h to completely assemble to obtain Mel / Ma-κca. Then 5% (wt / v) KCl solution was slowly added to initiate crosslinking to obtain physically crosslinked Mel / Ma-κca gel; then 6.9 mW / cm 2After irradiating with ultraviolet light for 40 seconds to complete the photocrosslinking reaction, it was quickly poured into a mold to obtain a physical-chemical double crosslinked Mel / Ma-κca gel. After cooling naturally, it was washed three times with deionized water and the surface moisture was dried. It was then transferred to a -20℃ freeze dryer and frozen for 2 hours and then continued to be frozen in a -50℃ freeze dryer for 1 hour, so that the Mel / Ma-κca gel maintained its flexibility while giving it abundant pores. Finally, the sample was collected in a sample bag and stored in a dark place to ensure that the entire operating environment was completely dark-proof.
[0027] The Mel, κca, Ma-κca and Mel / Ma-κca gel materials prepared in the above examples were characterized and their performance tested.
[0028] (1) Fourier transform infrared spectroscopy (FTIR) characterization Characterization method: Using the potassium bromide tablet method, 1 mg of the sample was evenly mixed with 100 mg KBr and then tableted. The potassium bromide tablet was used as the background and scanned on an infrared spectrometer with a scanning range of 4000~500 cm -1 .
[0029] Results Analysis: The infrared spectra of Mel, κca, Ma-κca and Mel / Ma-κca porous gels are shown in Figure 1 As shown. Figure 1 It can be seen that at 1442cm -1 The peak at 1068 cm is attributed to aliphatic CH groups, and the peak at 1068 cm -1 The aliphatic CH groups at the positions are assigned to the C-OH stretching of phenolic compounds or aromatic rings in the substituted macromolecular system, which is consistent with the structural characteristics of phaeomelanopic pigments. -1 The band at 2910 cm is due to the stretching vibration of -OH. -1 The peak at 1360 cm corresponds to the stretching vibration of CH -1 and 1255cm -1 The absorption peaks at 1153 cm-1 correspond to the asymmetric stretching vibrations of S=O stretching and O=S=O sulfate ester in κ-carrageenan. -1 The bridge CO stretching vibration and 1076 cm -1 The characteristic band of CO stretching vibration at 1660 cm -1 The C=O characteristic ester peak appeared near the ester, confirming the successful methacrylation of κ-carrageenan.
[0030] In addition, at 929cm -1 and 850cm -1The peaks observed at 3500 cm-1 are the stretching vibration of CO in polyhydroxyl groups and the stretching vibration of CO-SO3 in d-galactose-4-sulfate. In the Mel / Ma-κca porous gel material, the addition of Mel covers a large number of hydrogen bonds of Ma-κca, which is located at 3500 cm-1. -1 The nearby peaks shifted or merged into new peaks. These results further indicate that Mel and Ma-κca are not simply mixed but interact with each other.
[0031] (2) Scanning electron microscopy (SEM) and water contact angle characterization Characterization method: The freeze-dried gel was observed using a scanning electron microscope (SEM) to analyze its surface morphology. The dry gel after gold spraying was placed in the SEM and photographed under pressure. During the shooting process, the sample was always placed in a vacuum environment and the shooting voltage was 15kV. At the same time, a surface contact angle tester was used to measure the water contact angle value and analyze the hydrophilicity of the sample.
[0032] Results analysis: Scanning electron microscopy (SEM) images clearly show the changes in the surface morphology of κca before and after cross-linking and grafting with Mel. Figure 2 As shown in the figure, it can be observed that the sample surface has an irregular porous structure. Figure 2 (a) shows that the average pore size of uncrosslinked κca is about 200 μm. Figure 2 (b) shows that the Ma-κca that has completed photocrosslinking and potassium ion crosslinking has more abundant pores, with an average diameter of about 100μm, which indicates that more networks are formed during the double crosslinking process, and more micropores are generated during the subsequent freeze-drying regulation process. The micropores in these networks can allow the Mel / Ma-κca adsorption material to have a larger comparative area during the adsorption process, thereby greatly improving the adsorption performance.
[0033] exist Figure 2 In (c), it can be observed that the introduction of Mel into the gel structure did not damage the gel network. The water contact angle is an indicator of the wettability parameters of the material surface. The larger the angle, the worse the surface wettability and the stronger the hydrophobicity of the material. The κca-based gel materials all showed good hydrophilicity (κca≤38.1°, Ma-κca≤23.3°, Mel / Ma-κca≤22.4°), and their hydrophilicity did not change significantly after grafting Mel, proving that Mel has been grafted into the 3D network of the gel material.
[0034] (3) Thermogravimetric (TG) characterization Characterization method: The thermal stability of the sample was measured at a constant heating rate of 10°C / min, from 25°C to 700°C, and a nitrogen flow rate of 400mL / h. The weight loss of the sample with increasing temperature was measured, and the DTG curve was obtained by calculation and derivation.
[0035] Result analysis: The thermal decomposition process of κca, Ma-κca, and Mel / Ma-κca porous gel materials was analyzed by TGA. Figure 3 ).from Figure 3 It can be seen that the thermal decomposition process of κca and Ma-κca went through three stages. The first stage occurred in the range of 25~130℃, and part of the free water inside the material and the bound water on the surface evaporated, causing its mass to decrease by about 10%, and the thermal decomposition phenomenon was relatively gentle. In the second stage, in the range of 240~260℃, the thermal decomposition rate of κca and Ma-κca increased significantly, and the mass decreased by about 26.2%. Figure 4 The peak value of the derivative thermogravimetric curve (DTG) shows that the weight loss rate reaches the maximum value at 250°C, which is caused by the dehydration of some -OH and -COOH in the material and the decomposition of glycosidic bonds into intermediate products. The third stage occurs at 260~700°C, and the pyrolysis rate gradually slows down, mainly due to the further decomposition of the intermediate products. The decomposition temperature of Mel / Ma-κca porous gel material in different intervals is higher than that of κca and Ma-κca, and only about 2% of the mass is lost in the range of 25~220°C, indicating that Mel / Ma-κca porous gel material has better thermal stability and can complete the adsorption process in a higher temperature environment.
[0036] (4) Mechanical properties measurement Mechanical strength is one of the important indicators for considering whether the adsorption material can be applied on a large scale. For this reason, we used a tensile testing machine to test the tensile strength of κca, Ma-κca, and Mel / Ma-κca porous gel materials.
[0037] Tensile property determination method: Cut the sample into a dumbbell shape with an initial gauge length of 12±0.5mm and a width of 2.5±0.2mm. The tensile test was carried out at room temperature (25°C) with a tensile rate of 10mm / min. Record the stress and strain data and draw the stress-strain curve.
[0038] Result analysis: Figure 5The stress-strain curves of the three gel materials show that all gels broke when the strain was between 1.3% and 2%. The introduction of the double cross-linking system in Ma-κca changed the intermolecular forces between -NH2 and -OH groups, improving the mechanical properties of the gel. After grafting natural melanin, the composite gel system still showed good tensile stress, which improved the overall mechanical strength of the gel system. The tensile stress of the Mel / Ma-κca porous gel material can be close to 0.22Mpa.
[0039] (5) Determination of swelling properties Determination method: Weigh a sample of a certain specification, record the weight of the dry gel as W0, let it stand for a certain period of time at room temperature, then transfer it to ultrapure water, deionized water, tap water, and seawater solution to swell at time t, take out the sample and gently wipe the surface water with filter paper and weigh it. The wet weight at this time is recorded as Wt. Each group of tests is repeated three times. The swelling degree (SR) of the sample is calculated by formula (1-1); the water retention rate (Wr) is calculated by formula (1-2).
[0040] (1-1) (1-2) in, (g / g) Swelling degree of the sample, (g) is the mass of the gel in the dry state, (g) is the mass of the gel at time t, Wr (%) is the water retention rate of the gel material within 5 h, and Ws (g) is the mass of the gel after swelling and saturation for 5 h.
[0041] Result analysis: The swelling curves of κca, Ma-κca, and Mel / Ma-κca porous gel materials over time are shown in Figure 2. Figure 6 As shown in the figure, the swelling trends are similar during the whole swelling process. They all swell rapidly within 15 minutes, then the swelling degree tends to be slow and stable, and reaches the extreme value around 100 minutes.
[0042] In order to investigate the acid and alkali resistance of the adsorbent material, the swelling properties of the gel material were tested under different pH conditions. Figure 7 It shows that the κca, Ma-κca, and Mel / Ma-κca porous gel materials have low swelling degrees in acidic environments. When the pH value gradually increases, the H+ in the aqueous solution decreases, and the carboxyl and amide groups are ionized. At high pH values, the negative charge of the polyelectrolyte increases, and the electrostatic repulsion increases. Therefore, the swelling degree of the gel increases. When the pH value is around 7, the swelling degree of the Mel / Ma-κca porous gel material reaches a maximum value of 798.19 g / g, which is much higher than 507.44 g / g of κca.
[0043] The application of adsorption materials in different scenarios was tested, and the results were as follows: Figure 8 and 9 shown. Figure 8 The effects of simulating different water bodies (ultrapure water, deionized water, tap water, seawater) on the swelling properties of the gel were demonstrated. Compared with ultrapure water (798.19 g / g) and deionized water (934.46 g / g), the swelling degrees of the gel material in other water bodies (tap water: 497.33 g / g, seawater: 334.15 g / g) decreased to varying degrees, with seawater being the most obvious. This may be because seawater contains more types of anions and cations and their concentrations are higher than those in ultrapure water, deionized water and tap water. The high concentration of Na + This will cause the polymer chains of the gel to self-aggregate, thereby reducing the degree of swelling.
[0044] Water retention rate can evaluate the water holding capacity of materials. Fig. 9 The results show that the water retention rates of Mel / Ma-κca porous gel materials in different water bodies (ultrapure water: 86.57%, deionized water: 91.65%, tap water: 93.15%, seawater: 96.72%) are higher than those of κca and Ma-κca. This is because the addition of Mel can not only increase the degree of cross-linking, but also promote the water retention function of the gel.
[0045] (6) Experimental test on dual adsorption performance of antibiotics and heavy metals Test method: configure each metal ion (Cu 2+ Cr 6+ ) with an initial concentration of 100 mg / L, antibiotics (TC, SD) with an initial concentration of 50 mg / L, and Cu 2+ -TC and Cr 6+ 50 mL of each -SD binary system was placed in a 150 mL conical flask, and 80 mg of the prepared Ma-κca and Mel / Ma-κca adsorbent materials were added respectively. After adjusting the pH value of the solution to 7, the conical flask was placed in a constant temperature oscillator, the temperature was adjusted to 25 ° C, the speed was adjusted to 150 rpm, and the sampling interval was 5 min. The sample was filtered with a 0.45 μm PES membrane and then the concentration was determined.
[0046] Results analysis (such as Fig.10 After adsorption, the Mel / Ma-κca is located at 3500cm -1 The -OH functional group peak shifted to 3800 cm -1 The intensity of the absorption peak also changed, indicating that heavy metal ions and antibiotic molecules had ion exchange or complexation with -OH in the Mel / Ma-κca porous gel network. -1The amino absorption peak at the position shifted, indicating that the amino nitrogen atom in Mel / Ma-κca and Cu 2+ and Cr 6+ The absorption peak of Mel / Ma-κca at about 1060cm-1 is the stretching vibration peak of CO of primary alcohol, which is offset relative to Mel / Ma-κca, indicating that the carboxyl group participates in the reaction and the metal ion coordinates with the carboxyl group and amino group in Mel / Ma-κca to form a stable chelate. For the adsorption of antibiotic molecules, due to the expansion of the aromatic C=C group, the absorption peak of Mel / Ma-κca at about 1573cm-1 is the stretching vibration peak of CO of primary alcohol, which is offset relative to Mel / Ma-κca, indicating that the carboxyl group participates in the reaction and the metal ion coordinates with the carboxyl group and amino group in Mel / Ma-κca to form a stable chelate. -1 The peak shift was observed, indicating that there was π-π conjugation between the designed benzene ring-containing adsorbent and the aromatic rings in the pollutants. -1 The COC peak intensity increases, indicating that H in -OH is replaced during the adsorption process, resulting in a reduction in -OH, further proving that electrostatic adsorption and hydrogen bonding are involved in the adsorption process. In addition, in the binary system, some peaks corresponding to C=O and CO can be observed to shift, weaken, or even disappear, indicating that these functional groups are involved in the formation of coordination complexes with heavy metals and TC.
[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a carrageenan-based adsorption material, characterized in that: The following steps are involved: (1) Extraction of natural melanin from apricot shell; (2) Using the Ma photosensitive group to esterify κca to synthesize Ma-κca; (3) The extracted natural melanin is grafted onto the Ma-κca network to prepare the melanin / Ma-κca porous gel adsorption material.
2. The method for preparing a carrageenan-based adsorption material according to claim 1, characterized in that: The specific operations of step (1) are: The dried apricot shell is crushed and sieved, dissolved in NaOH solution at a solid-liquid ratio of 1:15, and the solid is removed after standing. The pH of the supernatant is adjusted with dilute HCl, and the supernatant is removed after standing and settling. The pH of the precipitate is adjusted with deionized water, and then 0.1% of cellulase and saccharifying enzyme are added. The supernatant is removed by centrifugation after heating in a water bath, and NaOH solution is added to the enzyme-treated solid at a solid-liquid ratio of 1:20, ultrasonically dissolved, acid precipitated and centrifuged to remove the supernatant. The solid obtained after drying is melanin, which is sealed in a dark place.
3. The method for preparing a carrageenan-based adsorption material according to claim 2, characterized in that: The concentration of NaOH solution is 2 mol / L, and the pH is adjusted to 2.2 with dilute HCl; the pH is adjusted to 5.0 with deionized water; the solution is heated to 60°C in a water bath and sealed at 4°C to avoid light.
4. The method for preparing a carrageenan-based adsorption material according to claim 1, characterized in that: The specific operations of step (2) are: κca with a mass volume percentage concentration of 2% was added to deionized water and dissolved at 80°C, and then Ma was added to react at 50°C. The pH value of the solution was kept constant during the reaction. After the reaction was completed, dialyzed to obtain a pure Ma-κca solution, which was freeze-dried and stored away from light.
5. The method for preparing a carrageenan-based adsorption material according to claim 4, characterized in that: The pH value of the solution was 8.0; the dialysis conditions were: dialysis at 4°C for 3 days using a 14 kDa cut-off dialysis bag; the freeze-drying temperature was -80°C, and the storage temperature was -20°C.
6. The method for preparing a carrageenan-based adsorption material according to claim 1, characterized in that: The specific operations of step (3) are: The Ma-κca macromer and unmodified κca were added to a photoinitiator with a mass volume percentage concentration of 0.25%, and dissolved at 80°C to obtain a Ma-κca solution. The extracted apricot shell melanin was dissolved in a 2 mol / L NaOH solution, and added to the Ma-κca solution at 50°C with stirring to obtain Mel / Ma-κca. A KCl solution with a mass volume percentage concentration of 5% was added as an initiator to initiate crosslinking to obtain a physically crosslinked Mel / Ma-κca gel, which was then rapidly poured into a mold after ultraviolet irradiation to complete the photocrosslinking reaction to obtain a physically-chemically double crosslinked Mel / Ma-κca gel. The gel was washed with deionized water after cooling, and the surface moisture was dried and stored in a frozen state away from light.
7. The method for preparing a carrageenan-based adsorption material according to claim 6, characterized in that: The freezing process is: first transfer to a -20°C freeze dryer for 2 h, and then transfer to a -50°C freeze dryer for 1 h.
8. A carrageenan-based adsorption material, characterized in that: The adsorption material is prepared by the preparation method according to any one of claims 1 to 8.
9. The use of a carrageenan-based adsorption material according to claim 8, characterized in that: The adsorption material is used for dual adsorption of antibiotics and heavy metals.